2002
DOI: 10.1515/hf.2002.015
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Liquids and Swelling of Wood. Part VI. Saturated Amounts and Some Thermodynamic Values of Adsorption

Abstract: To understand the swelling phenomenon of wood in liquids, the saturated amount of adsorption of liquids onto wood and the standard free energy changes of the adsorption were determined. The saturated amount of adsorption obtained by regression for several liquids decreased with increasing molecular size of the solvents. The mechanism of wood swelling is discussed systematically taking all the liquids examined in previous experiments into account. Since methanol molecules require more energy for release from co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 6 publications
(11 reference statements)
0
4
0
Order By: Relevance
“…With the increase of RH, the EMC of Quercus spp. and X. melanoxylon gradually became smaller than that of Z. schneideriana and Carpinus L, which may be due to the high density and extract content, resulting in low expansion rate and reduced multi-layer molecular adsorption (Morisato et al 2002). The EMC of Carpinus L was always lower than that of Z. schneideriana because the content of Z. schneideriana holocellulose was high and the crystallinity was lower than that of Carpinus L. In phase D, the EMC of the four kinds of wood decreased with the increase of tree species density, which may be due to the minimum density of Z. schneideriana and the high content of holocellulose.…”
Section: Wood Density Chemical Composition Content and Crystallinitymentioning
confidence: 96%
See 2 more Smart Citations
“…With the increase of RH, the EMC of Quercus spp. and X. melanoxylon gradually became smaller than that of Z. schneideriana and Carpinus L, which may be due to the high density and extract content, resulting in low expansion rate and reduced multi-layer molecular adsorption (Morisato et al 2002). The EMC of Carpinus L was always lower than that of Z. schneideriana because the content of Z. schneideriana holocellulose was high and the crystallinity was lower than that of Carpinus L. In phase D, the EMC of the four kinds of wood decreased with the increase of tree species density, which may be due to the minimum density of Z. schneideriana and the high content of holocellulose.…”
Section: Wood Density Chemical Composition Content and Crystallinitymentioning
confidence: 96%
“…and X. melanoxylon have higher wood density, high extractives content, and compact structure. When the sample thickness increases, it is difficult for water to enter the wood, with less hydrogen bond fracture and volumetric expansion produces fewer cracks (Mantanis et al 1994;Morisato et al 2002), resulting in reduced EMC.…”
Section: Wood Density Chemical Composition Content and Crystallinitymentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile Mantanis et al 4,5 performed a precise measurement on the swelling rate of wood in various liquids and they concluded that the apparent activation energy in the swelling process well corresponded to that for the scission of internal hydrogen bonds among wood constituents. In recent thermodynamic approaches by Morisato et al [6][7][8] they discussed the cohesive interaction within the bulk liquids in the phased adsorption processes of wood. Although the correlations between wood swelling and liquid properties are not always clear, it is generally accepted that the swelling of wood involves competitive processes of the adsorption by hydrogen bonding and the scission of internal hydrogen bonds between the amorphous molecules of wood constituents, therefore it depends on the hydrogen bonding properties of liquids.…”
Section: Introductionmentioning
confidence: 99%